Guided by Identities? A Constructivist Approach to Sino-American Relations - Pardo, Ramón Pacheco (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2014)
Abstract The nature of the relationship between the US and China has become one of the most discussed topics in the field of IR. Contrary to Realist expectations, this relationship has thus far been characterized by cooperation on a wide range of issues rather than permanent conflict. Proponents of socialization maintain that this has been the result of Chinese integration within existing institutions and norms. Differently, this article argues that Sino-American cooperation stems primarily from each country’s self-images, perceptions of the Other, and the interests associated with them. American ideas of Exceptionalism, Chinese notions of Tianxia and modernization, and mutually positive perceptions of each other, dating back to the late 18th century, underpin a set of interests that explain why current Sino-American relations are characterized by a high degree of cooperation.